Optical and Infrared Spectroelectrochemical Studies of CN-Substituted Bipyridyl Complexes of Ruthenium(II) - Taylor, James O; Pižl, Martin; Kloz, Miroslav; Rebarz, Mateusz; McCusker, Catherine E; McCusker, James K; Záliš, Stanislav; Hartl, František; Vlček, Antonín (Inorganic chemistry, 2021)
Ruthenium(II) polypyridyl complexes [Ru(CN-Me-bpy) (bpy) ] (CN-Me-bpy = 4,4'-dicyano-5,5'-dimethyl-2,2'-bipyridine, bpy = 2,2'-bipyridine, and = 1-3, abbreviated as , , and ) undergo four ( ) or five ( and ) successive one-electron reduction steps between -1.3 and -2.75 V versus ferrocenium/ferrocene (Fc /Fc) in tetrahydrofuran. The CN-Me-bpy ligands are reduced first, with successive one-electron reductions in and being separated by 150-210 mV; reduction of the unsubstituted bpy ligand in and occurs only when all CN-Me-bpy ligands have been converted to their radical anions. Absorption spectra of the first three reduction products of each complex were measured across the UV, visible, near-IR (NIR), and mid-IR regions and interpreted with the help of density functional theory calculations. Reduction of the CN-Me-bpy ligand shifts the ν(C≡N) IR band by ca. -45 cm , enhances its intensity ∼35 times, and splits the symmetrical and antisymmetrical modes. Semireduced complexes containing two and three CN-derivatized ligands , , and show distinct ν(C≡N) features due to the presence of both CN-Me-bpy and CN-Me-bpy , confirming that each reduction is localized on a single ligand. NIR spectra of , , and exhibit a prominent band attributable to the CN-Me-bpy moiety between 6000 and 7500 cm , whereas bpy -based absorption occurs between 4500 and 6000 cm ; complexes , , and also exhibit a band at ca. 3300 cm due to a CN-Me-bpy → CN-Me-bpy interligand charge-transfer transition. In the UV-vis region, the decrease of π → π* intraligand bands of the neutral ligands and the emergence of the corresponding bands of the radical anions are most diagnostic. The first reduction product of is spectroscopically similar to the lowest triplet metal-to-ligand charge-transfer excited state, which shows pronounced NIR absorption, and its ν(C≡N) IR band is shifted by -38 cm and 5-7-fold-enhanced relative to the ground state.